Payment collection efficiency in Syarikat Air Melaka Bhd / Siti Salwa Sahat - Sahat, Siti Salwa (2012)
Water is a fundamental necessity for all forms of life, of course, as well as to all the activities of human society. This paper describes the payment collection efficiency in Syarikat Air Melaka Bhd. This company is holding too much non-payment collection, hence, this study will investigates the payment collection of this company either it is efficient or not. This study also will identify the problem in the payment collection to discover any reason that leads to holding too much non-payment and find solution to the problem. The paper also will discover either disconnection of water by the company is efficient to enforce payment. Using primary and secondary data, the information is gathered so that the finding and gap analysis can be achieved. It can be seen that there are few factors that influenced the judgement of consumers to become payers or non-payers. It is agreed by others researcher that payers and non-payers have similar profile background, it concluded that the disconnection done by the company is not efficient since their non-payment collection is higher that disconnection by them. Moreover, this paper finds that there are certain obstacles that make the disconnection failed.